2019
DOI: 10.1038/s41598-019-44894-w
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological factors help to predict lymph node metastases more efficiently than extra-nodal recurrences in submucosa invading pT1 colorectal cancer

Abstract: The therapeutic management of patients with endoscopic resection of colorectal cancer invading the submucosa (i.e. pT1 CRC) depends on the balance between the risk of cancer relapse and the risk of surgery-related morbidity and mortality. The aim of our study was to report on the histopathological risk factors predicting lymph node metastases and recurrences in an exhaustive case series comprising every pT1 CRC (of adenocarcinoma subtype only) diagnosed in Finistère (France) during 5-yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 41 publications
1
26
2
Order By: Relevance
“…As others, we found that 8.5% of LPs were T1 CRCs (9.3% of them N1) and 15.9% of them were cured by ER (16.3% in a French population-based study (32,34). These rates were significantly lower in pedunculated LPs (6.1%, 5.4% and 37.8%, respectively) than in non-pedunculated LPs (10.8%, 11.4% and 4.3%, respectively).…”
Section: Discussionsupporting
confidence: 63%
“…As others, we found that 8.5% of LPs were T1 CRCs (9.3% of them N1) and 15.9% of them were cured by ER (16.3% in a French population-based study (32,34). These rates were significantly lower in pedunculated LPs (6.1%, 5.4% and 37.8%, respectively) than in non-pedunculated LPs (10.8%, 11.4% and 4.3%, respectively).…”
Section: Discussionsupporting
confidence: 63%
“…Several reports have indicated the potential of ESD for diagnosing LNM in patients with T1 CRC 40,41 ; however, others suggest its diagnostic accuracy for LNM is still inadequate. 42 Because current clinical guidelines consider the presence of LNM an important risk factor for classifying a patient with T1 CRC as high risk, this highlights the need to develop robust biomarkers for LNM before treatment, which would be clinically transformative in selecting patients who truly require such invasive and radical surgical treatments. Our ability to successfully validate our signature in pretreatment serum samples underscores its clinical significance for improved treatment strategies in patients with T1 CRC, especially the ones who truly have LNM.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that TB status was significantly associated with disease-specific survival in colorectal cancer [16][17][18][19]. In addition, T stage and lymph node metastasis were shown to be related to TB status in colorectal cancer [20]. The prognostic relevance of TB status is well-established in colorectal cancers, which prompted the inclusion of this histopathologic characteristic in the recent WHO classification of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies showed that TB status was significantly associated with disease-specific survival in colorectal cancer [16][17][18][19]. In addition, T stage and lymph node metastasis were shown to be related to TB status in colorectal cancer [20]. Besides its prognostic relevance in colorectal cancer, it has been demonstrated that TB was associated with the prognosis of other cancer types, including esophageal, gastric, pancreatic, breast, and head and neck cancer in meta-analyses [21][22][23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%